2019
DOI: 10.3389/fonc.2019.00207
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide and Phenotypic Evaluation of Stem Cell Progenitors Derived From Gprc5a-Deficient Murine Lung Adenocarcinoma With Somatic Kras Mutations

Abstract: Lung adenocarcinomas (LUADs) with somatic mutations in the KRAS oncogene comprise the most common molecular subtype of lung cancer in smokers and present with overall dismal prognosis and resistance to most therapies. Our group recently demonstrated that tobacco carcinogen-exposed mice with knockout of the airway lineage G-protein coupled receptor, Gprc5a , develop LUADs with somatic mutations in Kras . Earlier work has suggested that cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…The ability of cultured cancer cells to grow as nonadherent spheroids is a potent predictor of tumor growth and is currently used to evaluate potential anticancer agents [28][29][30][31][32] . Three-dimensional in vitro cell culture techniques enable modeling of tumors and their microenvironments to aid in cancer drug discovery [33][34][35][36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…The ability of cultured cancer cells to grow as nonadherent spheroids is a potent predictor of tumor growth and is currently used to evaluate potential anticancer agents [28][29][30][31][32] . Three-dimensional in vitro cell culture techniques enable modeling of tumors and their microenvironments to aid in cancer drug discovery [33][34][35][36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the qRT-PCR preliminary results of the cultivated spheres (n = 1) showed that the increase in the sulfation of biomimetic GAGs led to the decrease in the stemness properties of CSCs by down-regulation of some CSCs' markers ( Figure S5) [49][50][51][52][53][54][55][56]. Results showed downregulation of ALDH1A1 and ALDH3A1 in H1792 cells and Aldh1a1 in MDA-F471 cells, which are known to be overexpressed in KRAS-mutant LUAD CSCs, the downregulation of CCL20 in H1792 and MDA-F471, which plays a major role in the growth and metastasis of lung cancer cells, and the downregulation of Alcam and Tnf in MDA-F471, epithelial cell marker and proinflammatory cytokine, respectively [48]. These findings are consistent with other studies that stated the effects of anti-tumor agents on the CSC population using sphere-forming assay [46][47][48][49][50]57,58].…”
Section: Discussionmentioning
confidence: 96%
“…Results showed downregulation of ALDH1A1 and ALDH3A1 in H1792 cells and Aldh1a1 in MDA-F471 cells, which are known to be overexpressed in KRAS-mutant LUAD CSCs, the downregulation of CCL20 in H1792 and MDA-F471, which plays a major role in the growth and metastasis of lung cancer cells, and the downregulation of Alcam and Tnf in MDA-F471, epithelial cell marker and proinflammatory cytokine, respectively [48]. These findings are consistent with other studies that stated the effects of anti-tumor agents on the CSC population using sphere-forming assay [46][47][48][49][50]57,58]. Furthermore, they motivate further investigations to determine the ability of AlgSulf n to target and affect CSCs growth and the pathway that is affected by the AlgSulf n .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations